2011
DOI: 10.1007/s15010-011-0162-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Herpes zoster in patients with underlying diseases: a retrospective hospital-based cohort study

Abstract: PurposeTo determine the incidence of Herpes zoster in patients with one of 17 specific underlying diseases compared with that in patients with other underlying diseases.MethodsWe conducted a retrospective hospital-based cohort study using data from patients’ electronic medical records for the period 2001–2007 of the Kitano Hospital Research Database. These analyses included 55,492 patients with one of 17 underlying diseases, which were those reported as related to the contraction of Herpes zoster. Of these, 76… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
120
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(133 citation statements)
references
References 26 publications
7
120
1
5
Order By: Relevance
“…Malignite varlığı, AİDS, otoimmün hastalık, SLE, romatoid artrit, psikolojik bozukluklar, majör depresyon, DM, hipertansiyon, konjestif kalp yetmezliği, operasyon, radyoterapi, kemoterapi, travma gibi bağışıklık sistemini baskılayan hastalıklar ve/ veya tedaviler HZ gelişimini kolaylaştırmakta ve görülme sıklığı %30-50'ye kadar çıkmaktadır [10][11][12] . İmmün sistemi güçlü olan hastalarda dermatom tutulumuna bağlı oluşan ağrı, postherpatik nevralji, bakteriyel süperinfeksiyon gibi semptomlar immün sistemi zayıflamış hastalarda daha şiddetli seyretmektedir [4][5][6]11,12 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Malignite varlığı, AİDS, otoimmün hastalık, SLE, romatoid artrit, psikolojik bozukluklar, majör depresyon, DM, hipertansiyon, konjestif kalp yetmezliği, operasyon, radyoterapi, kemoterapi, travma gibi bağışıklık sistemini baskılayan hastalıklar ve/ veya tedaviler HZ gelişimini kolaylaştırmakta ve görülme sıklığı %30-50'ye kadar çıkmaktadır [10][11][12] . İmmün sistemi güçlü olan hastalarda dermatom tutulumuna bağlı oluşan ağrı, postherpatik nevralji, bakteriyel süperinfeksiyon gibi semptomlar immün sistemi zayıflamış hastalarda daha şiddetli seyretmektedir [4][5][6]11,12 .…”
Section: Discussionunclassified
“…Yaşlılık, travma, stres ve immün süpresyonu virüsü aktifleştiren önemli faktörler arasında yer almaktadır. Yapılan çalışmalarla HZ'nin yaşla görülme sıklığının arttığı ve yaşlı erkeklerde kümelenmenin olduğu bilinmektedir 3,6,10,11,18,19 . Donahou ve ark.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…An increased risk of HZ, which in any case is age-related, is also associated to some underlying medical conditions as diabetes, Chronic Obstructive Pulmonary Disease (COPD), in addition to stressful events/traumatic events, immunosuppression and immunosuppressive treatments. 1,30,31 Some chronic diseases are possibly associated with an altered functionality of the cell-mediated immune response (CMI) which can lead to an increase of HZ cases. 32 Some researches suggest that patients with HZ are more likely to have a history of myocardial infarction, hypertension, heart failure, diabetes mellitus, asthma, and COPD.…”
Section: Which Are the Main At Risk Groups?mentioning
confidence: 99%
“…33 A retrospective cohort study found that patients with diabetes mellitus, kidney failure, cancer and other conditions have a risk of developing shingles 1.8-8.4 times higher than patients with other diseases. 31 A case-control study conducted in the US population found that the risk of developing HZ was significantly greater in patients who had risk factors (diabetes, cardiovascular disease, COPD). The same study found that 7.6% of the considered population was suffering from immunosuppression.…”
Section: Which Are the Main At Risk Groups?mentioning
confidence: 99%